Elevated level of cerebrospinal fluid and systemic chemokine CCL5 is a predictive biomarker of clinical outcome after aneurysmal subarachnoid hemorrhage (aSAH). (September 2020) - Chaudhry, Shafqat Rasul; Kinfe, Thomas Mehari; Lamprecht, Alf; Niemelä, Mika; Dobreva, Gergana; Hänggi, Daniel; Muhammad, Sajjad
Highlights: Chemokine C-C motif ligand 5 (CCL5) was significantly elevated during early and delayed brain injury phases after aneurysmal subarachnoid hemorrhage (aSAH). Serum CCL5 levels were significantly lower on day 7 after aSAH in patients developing chronic hydrocephalus, pneumonia infection and who have additional intracerebral bleeding. CSF CCL5 levels increased on day 1 after aSAH in patients developing chronic hydrocephalus, delayed ischemic neurological deficits and intraventricular hemorrhage. CCL5 levels correlated with clinical outcome. Abstract: Background: Pathophysiology of aneurysmal subarachnoid hemorrhage (aSAH) is highly complex. Bleeding from ruptured aneurysm causes increase in intracranial pressure that disrupts blood-brain barrier leading to infiltration of peripheral immune cells. Interactions between the infiltrated leukocytes and the resident brain cells in the injured tissue mainly determine the delayed tissue damage. Recruitment of leukocytes in the injured brain is mainly mediated by the chemokines. Chemokine C-C motif ligand 5 (CCL5) is a potent pro-inflammatory chemokine shown to be upregulated in preclinical SAH studies. However, detailed clinical investigations exploring the association of cerebrospinal fluid (CSF) and systemic CCL5 and post-aSAH complications and clinical outcome are still lacking. This study investigated CSF and systemic CCL5 after aSAH and its association with clinical outcome and post-aSAH complications. Methods: CSF and serum from control and aSAH patients were obtained after centrifugation of the CSF and peripheral blood, and were preserved at −80 °C until quantification by an enzyme-linked immunoassay. Patient pertinent data, post-aSAH complications and clinical outcome (modified Rankin scale [mRS] and Glasgow outcome scale [GOS]) were retrieved from patient records. Results: A significant increase in CSF and serum CCL5 levels was observed on post-aSAH day 1 and day 7 compared to control patients. Dichotomization of patients to poor (mRS 3–6 or GOS 1–3) and good (mRS 0–2 or GOS 4–5) clinical outcomes showed significantly higher serum CCL5 levels in patients with good clinical outcome at discharge, but lower CSF CCL5 levels. Interestingly, significantly lower serum CCL5 levels were observed on post-aSAH day 7 in patients who have additional intracerebral bleeding or the patients who developed chronic hydrocephalus or pneumonia. Whereas, CSF CCL5 levels significantly increased on post-aSAH day 1 in patients developing chronic hydrocephalus, delayed ischemic neurological deficits and intraventricular hemorrhage. CSF CCL5 levels on post-aSAH day 1 were correlated with poor clinical outcome, however, serum CCL5 levels on post-aSAH day 7 were correlated with good clinical outcome. Conclusion: Systemic and CSF CCL5 levels were elevated after aSAH and levels of serum CCL5 on day 7 were associated independently with clinical outcome (GOS and mRS) at discharge. Therapeutic approaches targeting CCL5 might be beneficial in aSAH.